MODEL TABUNGAN RUMAH TANGGA KOTA SEMARANG - Sumastuti, Efriyani (JEJAK: Jurnal Ekonomi dan Kebijakan, 2009)
The study is aimed to estimating the household saving model appropriately applied in Semarang city.A cross-section household survey was conducted in Semarang city. The survey included two hundredand seventy selected samples and 5 stratified occupational background of the head of the family; (1)farmer and fisherman, (2) labor, (3) businessman, (4) civil servant, military members, and police officers,(5) retired persons and others. Life Cycle Hypothesis (LCH), Permanent Income Hypothesis (PIH), LifeCycle Ã¢â¬â Permanent Income Hypothesis (LC-PIH) and the extended LC-PIH, estimated with the log-linearOLS method, were employed to analyze and select the best household saving model. The estimationresult showed that the best model was LC-PIH II, whereas the best model in accordance with the type ofoccupation was the following (1) Labor: LC-PIH III, (2) Businessman: PIH, (3) Civil Servant, MilitaryMembers, and Police Officers: LC-PIH II and (4) Retired Persons and others: LC-PIH II. The synthesizedmodel of LC-PIH gives an important contribution on the household saving model. Besides, study in thesame field with the two additional variables in the LC-PIH model (insurance and rational expectations) aswell as five stratified occupations had not been conducted. Finally, further study is needed, especiallythose which include more specific sample and the usage of different model and stratification.Keywords: household saving, occupation, LC-PIH model